Piąta część "Villanelle" Pawła Szymańskiego w świetle teorii mieszanin pojęciowych - Kostka, Violetta (Res Facta Nova, 2022)
Conceptualization, that is, the recognition of cognitive intuitions in concepts, is one of the basic topics of cognitive science. One of the most popular theories of this type is the conceptual blending theory by Gilles Fauconnier and Mark Turner. The aim of this article is to present the main assumptions of this theory and to interpret in its light one work by Paweł Szymański, namely the fifth movement of Villanelle for countertenor, two violas and harpsichord to the poem by James Joyce. Interpretation has several stages. At the beginning, two sets of concepts necessary for creating blends are established: the first relating to the poetic layer of the work, and the second ‒ to its musical layer. Next, the author discusses three intra-musical stylistic blends. The first is characterized by a clear dominance of concepts concerning baroque devices over modernist ones, the second ‒ by inverse proportions of devices, and the third is a similar kind of polystylism as the first. Finally, the subject of consideration are the extra-musical blends leading to the creation of three main meanings of the work. They can be summarized as the following story about the poetical and musical Persona: he begins by practising some form of love ritual in mythical/sacred time; after a fairly long time in a lethargic state, he comes closer to reality and thinks about love from the perspective of his own body and clarity; finally, he drowns in a previously performed ritual within mythical/sacred time. The article is supplemented by the poem, the table with the characteristics of the three episodes, two musical examples and four diagrams with networks of integrated concepts.